(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This study examines the impact of motivation and work environment on employee performance at PT. Mandiri Utama Finance. The researchers argue that motivation and work environment are crucial factors in determining employee performance, as they can either enhance or hinder employee productivity and job satisfaction. The study aims to identify the most influential factors of motivation, both intrinsic and extrinsic, and the aspects of the work environment that affect employee performance. The results of the study are expected to provide valuable insights for management to develop strategies and policies that can improve employee motivation and create a supportive work environment, ultimately leading to enhanced employee performance. The study contributes to the development of theory and knowledge in the field of Human Resource Management, providing a practical guide for organizations to improve employee performance.